Seismic behavior of Four-Part Vertically Isolated Structure (FPVIS) with viscous dampers in multi-story regular steel buildings - Yazdani, Samira; Nekooei, Masoud; Hosseini, Mahmood; Jafari, Mohammad Ali (Taylor & Francis Ltd, 2025)
This study proposes a novel method to enhance energy dissipation in building structures by partitioning three-dimensional building's skeleton into four parts, two short-period (stiff) and two long-period (soft), interconnecting by linear viscous dampers. First, a set of 3-, 5-, and 10-story regular steel buildings were designed using the conventional design code. Then, each building's skeleton was divided into four architecturally equal parts of the same mass, but different stiffness values, and optimal damping coefficient values were found by trial and error, to minimize the seismic responses, obtained by nonlinear time history analyses (NLTHA). To conduct NLTHA, three-component records of eleven site-compatible earthquakes were selected, and the seismic responses, including Inter-story drift, roof absolute acceleration, base shear forces, and dampers' force-displacement hysteresis, were obtained. The results demonstrated, on average, a decrease of 43% in drift values, and 41% in base shear forces was achieved using optimal dampers. Roof absolute acceleration was reduced by 47% and 66% for stiff and soft substructures, respectively. Finally, a comparison of the created plastic hinges, in the two groups of structures revealed that their performance in the four-part vertically isolated structures remains at the IO level, while in the single-part structures, they mostly exceed the LS level.
Keywords: Stiff and soft substructures; linear viscous dampers; nonlinear time history analysis; seismic performance level; plastic hinges formation